An update on biology, diagnosis and treatment of primary plasma cell leukemia. Issue 4 (3rd April 2019) - Musto, Pellegrino; Statuto, Teodora; Valvano, Luciana; Grieco, Vitina; Nozza, Filomena; Vona, Gabriella; Bochicchio, Giovanni Battista; La Rocca, Francesco; D'Auria, Fiorella
ABSTRACT: Introduction : Primary plasma cell leukemia (PPCL) is one of the most aggressive hematological malignancies. The prognosis of PPCL patients remains poor, although some improvements have been made in recent years. Areas covered : In this review recent clinical and biological advances in PPCL are reported. Some recommendations for the practical management of these patients are provided, with a particular focus on the role of novel agents and transplant procedures. A brief description of the currently ongoing clinical trials with new drugs is also enclosed. Expert opinion : PPCL still represents a difficult challenge for all hematologists. Here the authors provide a personal view on how the current, generally unsatisfactory results in this neoplastic disorder could be improved. In particular, dedicated studies exploring alternative therapies are necessary and eagerly awaited. Such studies should possibly be based on new biological information that could be of help in identifying novel genetic biomarkers for risk stratification and new actionable molecular targets.